"They Don't Really Care": STEM Doctoral Students' Unsupportive Interactions with Faculty and Institutions - Theresa Elpidia Hernandez; Julie Posselt (MDPI AG, 2024)
Increasing the representation of racially minoritized groups and women in STEM graduate education is insufficient to make STEM fields and academia inclusive and equitable spaces, where all feel supported and thrive. This study was motivated by a phenomenological examination of support for graduate students, focusing on programs that admitted and graduated higher proportions of underrepresented students than their fields. We used negative case analysis to document the interplay of interpersonal and institutional interactions that define what racially/gender minoritized students experience as unsupportive. Guided by an intersectional interpretation of structuration, we uncovered three mechanisms-withholding support, doing racialized and/or gendered harm, and neglecting to take action when students faced known threats/harm-that underlie the unsupportive experiences faced by graduate students of color and women in STEM doctoral education. This typology of unsupportive mechanisms, alongside an understanding of positive types of support, can help practitioners and scholars rethink what constitutes support, moving toward creating equitable and inclusive graduate education.